Polymorphism of β-lactoglobulin (β-LG)|SacII gene and its association to milk protein and milk production in Saanen goats - R. Ambarwati; S. Sutopo; E. Kurnianto (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The objectives of this study were to analyze and identify the β-LG genotype and examine its association with milk protein and milk production of Saanen goats. Materials used in this study were DNA that originated from 22 Saanen does and its milk protein and milk production recording that was taken at 2,5; 3,0; 3,5 and 4,0 years old of Saanen does. DNA was analyzed using PCR-RFLP method with SacII restriction enzyme to identify genotype of B-LG gene and then were sequenced for each genotype. Sequencing data was analyzed using Clustal W in MEGA7.0, while association of B-LG gene genotype with milk protein and milk production was analyzed using General Linear Model (GLM) in SAS 9.0. The results showed that two alleles (A and G), forming two homozygous genotypes (AA and GG) and one heterozygous genotype (AG) were found, but there were no significant different within genotype on milk protein and milk production. In conclusion, there was no association between β-LG genotype and milk protein and milk production of Saanen goats.